HOW TO SECURE BASIC EVIDENCE AFTER AN AVIATION ACCIDENT - Robert KONIECZKA (Scientific Journal of Silesian University of Technology. Series Transport, 2017)
This article attempts to provide a synthesis of basic directions indispensable to accurately collecting evidence after an aviation accident. The proper collection procedure ensures the avoidance of the loss of evidence critical for an investigation carried out by law enforcement agencies and/or the criminal justice system, which includes the participation of aviation expert investigators. Proper and complete evidence is also used to define the cause of the accident in the proceedings conducted by Państwowa Komisja Badania Wypadków Lotniczych (State Committee for Aviation Incidents Investigation, The State Committee for Aviation Incidents Investigation, hereafter referred to as the PKBWL). The methodology of securing evidence refers to the evidence collected at the scene of an accident right after its occurrence, and also to the evidence collected at other sites. It also includes, within its scope, additional materials that are essential to furthering the investigation process, although their collection does not require any urgent action. Furthermore, the article explains the meaning of particular pieces of evidence and their possible relevance to the investigation process.